The Hidden History of a Third of the World: the Collective Biography of Australian and International Archaeology in the Pacific (CBAP) Project - Matthew Spriggs (Bulletin of the History of Archaeology, 2017)
The paper introduces a recently commenced five-year research project on the history of Pacific archaeology, the Collective Biography of Archaeology in the Pacific (CBAP) Project. The justification for the project, the background to it, its aims and some discussion of its initial stages and anticipated outcomes are given. At time of writing CBAP has been going for barely a year and so only a brief mention will be made of the research carried out so far during the initial establishment period.